(untitled) (European Journal of Pure and Applied Mathematics, 2025)
An M-homomorphism in an Almost Distributive Lattice(ADL) is introduced, with a sufficient condition for it to be an M-homomorphism. The image and inverse image of an M-filter under such a homomorphism are shown to be M-filters. Sufficient conditions for a prime filter to be an M-filter are established, along with an equivalence between prime M-filters and minimal prime filters. Finally, any two distinct prime M-filters in an ADL are shown to be comaximal.